Lessons From Systemic Bank Restructuring : A Survey of 24 Countries - Pazarbasioglu, Ceyla (IMF Working Papers; Working Paper ;, 1997)
In recent decades, a wide range of countries have experienced banking problems. Their approaches to systemic bank restructuring have varied substantially. This paper analyzes a representative sample of 24 countries and provides a summary of policies judged to be successful. The sample countries were ranked by relative progress in resolving banking sector problems. Based on this ranking, the paper examines the effectiveness of institutional and regulatory measures, assesses the impact of accompanying macroeconomic policies, and examines the extent to which particular restructuring instruments contributed to success. Special emphasis is given to the role of the central bank.